On the location of the eigenvalues of Jacobi matrices - Fonseca, C. M. da (2006)
Using some well known concepts on orthogonal polynomials, some recent results on the location of eigenvalues of tridiagonal matrices of very large order are extended. A significant number of important papers are unified.